2008
DOI: 10.4049/jimmunol.181.1.822
|View full text |Cite
|
Sign up to set email alerts
|

Complement Activation on B Lymphocytes Opsonized with Rituximab or Ofatumumab Produces Substantial Changes in Membrane Structure Preceding Cell Lysis

Abstract: Binding of the CD20 mAb rituximab (RTX) to B lymphocytes in normal human serum (NHS) activates complement (C) and promotes C3b deposition on or in close proximity to cell-bound RTX. Based on spinning disk confocal microscopy analyses, we report the first real-time visualization of C3b deposition and C-mediated killing of RTX-opsonized B cells. C activation by RTX-opsonized Daudi B cells induces rapid membrane blebbing and generation of long, thin structures protruding from cell surfaces, which we call streamer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
89
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(100 citation statements)
references
References 67 publications
(78 reference statements)
8
89
0
3
Order By: Relevance
“…In addition to the difference in binding sites between ofatumumab and rituximab, studies have suggested that ofatumumab dissociates more slowly from the cell surface than rituximab 35 and exhibits greater CDC activity than rituximab in various B cell lines. 35,48,75,77 Furthermore, CDC by ofatumumab was found to be less dependent on the cell-surface density of CD20 than CDC by rituximab. 48 The differential action of ofatumumab on the complement has been supported by direct visualization of complement-mediated cell killing obtained using spinningdisk confocal microscopy.…”
Section: Type II Cd20 Antibodiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the difference in binding sites between ofatumumab and rituximab, studies have suggested that ofatumumab dissociates more slowly from the cell surface than rituximab 35 and exhibits greater CDC activity than rituximab in various B cell lines. 35,48,75,77 Furthermore, CDC by ofatumumab was found to be less dependent on the cell-surface density of CD20 than CDC by rituximab. 48 The differential action of ofatumumab on the complement has been supported by direct visualization of complement-mediated cell killing obtained using spinningdisk confocal microscopy.…”
Section: Type II Cd20 Antibodiesmentioning
confidence: 99%
“…This could be expected to facilitate the deposition of activated complement on the cell surface and hence the amplification of the complement response. 77 However, the impact of this is unclear as the CD20 extracellular loop is very small compared with the size of an antibody so that the antibody-binding domain of CD20 is already membrane-proximal. In addition to the difference in binding sites between ofatumumab and rituximab, studies have suggested that ofatumumab dissociates more slowly from the cell surface than rituximab 35 and exhibits greater CDC activity than rituximab in various B cell lines.…”
Section: Type II Cd20 Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further in-vitro experiments indicated ofatumumab is effective in killing B-cells extracted from CLL patients. 14 …”
Section: Mini-reviewmentioning
confidence: 99%
“…Hybridoma that secreted human IgG1 anti-CD20 antibodies were extracted from successfully immunized mice. 13,14 Using genetic engineering techniques, heavy and light chain genes from one human anti-CD20 cell line, 2F2, were transfected into a murine myeloma cell line (NS/O) for production of ofatumumab.…”
Section: Origin and Preclinical Analysismentioning
confidence: 99%